Design e fabrica??o de um filtro rejeita-faixa para microondas baseado em superf?cies seletivas em frequ?ncia - Canga, Domingos Marcos (2018)
This work proposes the development of a monolithic resonance filter with reject-band behavior. This filter was based on frequency selective surface (FSS), as well as its numerical analysis. Grid geometry was used to allow greater flexibility in adjusting the frequency response. The proposed filter has a narrow operating band in the range of 1.4 to 1.6 GHz, with an attenuation of the order of 36 dB and a bandwidth of 6 MHz at the resonance frequency of 1.5 GHz. This filter exhibits adequate performance when exposed to high power radiation. Furthermore, it is a cost-effective design that can be printed using a conventional 3D printer. In this work, results are presented concerning the spectral characteristics of the filter, as well as the analysis of tolerance of the geometric parameters and the adjustment of the dielectric structure. Two geometric models were developed, one with the ends of the straight grid and the other with the ends of the bevelled grid. The reason for this was to observe the effect this causes on the frequency response of the filter.